Failure mechanism and bearing capacity of vertically loaded pile with partially-screwed shaft: Experiment and simulations. (February 2020) - Chen, Yadong; Deng, An; Lu, Fan; Sun, Huasheng
Abstract: An experimental and numerical investigation on performance of piles with partially-screwed shaft that were installed in sands was presented. Static load tests were conducted on a series of model piles to examine pile–sand interactions and the bearing capacity. The tested piles were varied in thread pitch in order to examine its effects on pile performance. Digital imaging correlations were used to visualise the failure slips of sands at locations of interest. The test results were used to validate a discrete element model (DEM) that was developed to assess the pile–sand interactions at micro-scale. The DEM model was applied to examine the effects of important pile geometric characteristics on the load transfer and bearing capacity of piles. The characteristics included the pitch, length of screw section, and shaft diameter. The simulation results suggested that the screw section and bottommost thread significantly influenced the pile bearing capacity. An optimum geometry of pile that maximised pile–sand interactions and prompted the pile performance was suggested.